Measuring the Role of Kiai and Santri in Creating the Spirit of Nationalism (Historical Approach in Reconstructing the Meaning of Jihad Resolution) - Syukur, Syamzan; Rohman, Moh. Mujibur; Rasyid, Suraya; ., Darusman; Syafii, Achmad Ghozali (Journal of Ecohumanism, 2024)
This article discusses the Jihad Resolution and the Nationalist spirit of the Islamic boarding school students (santri) in fighting for Indonesian independence because recently the Nationalist spirit of the Indonesian people has begun to erode, some even consider it an ideology that is contrary to Islam. By using a qualitative-historical approach and data collection techniques through literature study, this article wants to show that the spirit of Nationalism needs to be instilled in the souls of all the nation's children because it is the result of the Jihad Resolution to jointly defend and dedicate identity, integrity with the national spirit that was born by Hadratus Sheikh KH. Hasyim Asy'ari as a great scholar and founder of Nahdlatul Ulama (NU). Therefore, the opinion that Nationalism is a heretical ideology does not have a strong argument, especially when considering that Nationalism is excessive fanaticism which is prohibited makers that it is necessary to continuously instill the spirit of Nationalism by in religion. The results of this research can at least provide input to policy reviving the Jihad Resolution which is currently relevant to the nation's conditions. Jihad resolution does not mean physical war, but jihad can be actualized by a student in several aspects. Like; literacy jihad, jihad in the medical world, technology, economics, politics and other things relevant to.